Double Mycobacterial Infection in Septic Patient: A Rare Case of Pulmonary Tuberculosis and Leprosy Coinfection - Kirana Paramitha Santosa; Anggar Jito (The Indonesian Journal of General Medicine, 2026)
Introduction: Co-infection of Tuberculosis (TB) and Leprosy is a rare occurrence, even in endemic areas.1 This co-infection has higher risks of drug resistance, complications, and mortality.2,3 Case Report: A 38-year-old male patient, who had been taking long-term steroids, presented in severe condition, showing signs of sepsis and ARDS. Multilobar infiltrates were found in both lungs, MTB/RIF was positive and sensitive to Rifampicin, BTA was found in slit skin smear test, liver enzyme levels were elevated, D-dimer level was increased (6 mg/L), low PaO2/FiO2 ratio (44.25 mmHg), along with an increased AaDO2 (508.4 mmHg). Despite receiving antimicrobial and anti-tuberculosis therapy, the patient's condition continued to deteriorate, resulting in septic shock and death. Discussion: The rarity of these cases in the modern literature is likely due to Bacillus Calmette-Guérin (BCG) vaccination in endemic areas, which provides at least partial protection against both diseases. Dual infection is associated with higher morbidity (5.5%) and mortality (37.2%).2 Appropriate diagnostic, screening, and therapeutic regimens are needed in clinical practice to prevent the risk of drug resistance and complications. This study aimed to present a complicated case of pulmonary TB and multibacillary leprosy co-infection in a septic patient.